Role of polymers as crystal growth inhibitors in coprecipitation via solutionenhanced dispersion by supercritical fluids (SEDS) to improve andrographolide dissolution from standardized Andrographis paniculata extract - Lee, Sin Yee; Abdullah, Luqman Chuah; Abdul Rahman, Russly; Abas, Faridah; Chong, Gun Hean (Elsevier, 2019)
The poor aqueous solubility and dissolution rate of andrographolide in aqueous gastrointestinal fluids often cause low oral bioavailability. In this work, Andrographis paniculata extract containing 16% andrographolide was coprecipitated with Pluronic F127, Eudragit EPO, and Eudragit L100-55 via solution-enhanced dispersion by supercritical fluids (SEDS) to improve andrographolide dissolution in simulated intestinal fluid (pH 7.4). The SEDS working parameters were set constant as follows: 150 bar, 40 °C, CO2 flow rate 15 L/min (1 bar, 25 °C), liquid feed flow rate 0.5 mL/min, and 25 mg/mL of A. paniculata extract. SEDS coprecipitates formulated with lower Eudragit L100-55:A. paniculata mass ratios exhibited improved andrographolide dissolution in SIF (pH 7.4), while SEDS coprecipitates formulated with either Pluronic F127:A. paniculata or Eudragit EPO:A. paniculata at any mass ratio exhibited poorer andrographolide dissolution (<0.03 mg/mL released in 90 min) than SEDS-precipitated A. paniculata extract powder (0.06 mg/mL released in 90 min). In particular, SEDS coprecipitates formulated with a Eudragit L100-55:A. paniculata mass ratio of 6:25 were found to have the highest andrographolide release and dissolution rate in SIF (pH 7.4) (0.09 mg/mL released in 30 min). SEDS coprecipitation was successful, as indicated by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and Fourier-transform infrared (FTIR) analysis.